Costs of integrating cervical cancer screening at an HIV clinic in Kenya. Issue 2 (21st November 2016) - Vodicka, Elisabeth L.; Babigumira, Joseph B.; Mann, Marita R.; Kosgei, Rose J.; Lee, Fan; Mugo, Nelly R.; Okech, Timothy C.; Sakr, Samah R.; Garrison, Louis P.; Chung, Michael H.
Abstract: Objective: To estimate the societal‐level costs of integrating cervical cancer screening into HIV clinics in Nairobi, Kenya. Methods: A cross‐sectional micro‐costing study was performed at Coptic Hope Center for Infectious Diseases and Kenyatta National Hospital, Kenya, between July 1 and October 31, 2014. To estimate direct medical, non‐medical, and indirect costs associated with screening, a time‐and‐motion study was performed, and semi‐structured interviews were conducted with women aged at least 18 years attending the clinic for screening during the study period and with clinic staff who had experience relevant to cervical cancer screening. Results: There were 148 patients and 23 clinic staff who participated in interviews. Visual inspection with acetic acid was associated with the lowest estimated marginal per‐screening costs (3.30), followed by careHPV (18.28), Papanicolaou (24.59), and Hybrid Capture 2 screening (31.15). Laboratory expenses were the main cost drivers for Papanicolaou and Hybrid Capture 2 testing (11.61 and 16.41, respectively). Overhead and patient transportation affected the costs of all methods. Indirect costs were cheaper for single‐visit screening methods (0.43 per screening) than two‐visit screening methods (2.88 per screening). Conclusions: Integrating cervical cancer screening into HIV clinics would be cost‐saving from a societal perspective compared with non‐integrated screening. These findings could be used in cost‐effectiveness analyses to assess incremental costs per clinical outcome in an integrated setting. Abstract : The estimates generated suggested that integrating cervical‐cancer screening into HIV clinics would be cost‐saving from a societal perspective compared with non‐integrated screening approaches.